Analisis Faktor Non Performing Financing (NPF) pada Industri Perbankan Syariah - Maidalena, Maidalena (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2014)
This study aims to identify and analyze the influence of the Capital Adequacy Ratio (CAR) against Non-Performing Loans (NPLs) industry banking.